A decade of ecotourism research in protected areas: a bibliometric analysis / Mohammad Ridhwan Nordin and Salamiah A. Jamal - Nordin, Mohammad Ridhwan; A. Jamal, Salamiah (Research Management Centre (RMC), 2020)
The previous progress and future trend of ecotourism research are undergoing a significant paradigm shift in tourism research following the recent Covid-19 pandemic. The present study introduces a bibliometric review investigating of ten years publication between 2010 and 2020 in journal and proceeding documents. By adopting a bibliometric approach, this article addressed five key information's of journal and proceeding paper publications: (a) years and volume of publications (b) affiliation contribution (c) source and document type (d) the topic covers and (e) publication and intellectual knowledge. 37 relevant publications in the journal and proceeding paper were included in the study after excluding books, books series, chapter in book, thesis, citation document and several parameters. The trend of research on ecotourism has found a downward trend of productions produced per year, except in 2012. Moreover, marketing is the highest main topic of study. Such bibliometric analysis findings can be useful to find an opportunity for future study within the ecotourism setting, especially in protected areas such as national parks.